A kind of super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material and preparation method thereof

By using two-component polyurethane and epoxy resin cross-linked substrate layers, polyacrylate-siloxane hybrid self-adhesive layer, polyvinyl alcohol and boric acid cross-linked mucosa and self-healing microcapsules in the waterproof roll, the problem of insufficient performance of traditional rolls is solved, and higher weather resistance, self-adhesiveness and waterproofness are achieved, and it is suitable for building waterproofing applications in complex environments.

CN119736026APending Publication Date: 2025-04-01YUNNAN XINCHENG WATERPROOF TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411917473.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Traditional waterproof coils have insufficient performance in weather resistance, self-adhesion, waterproofness, chemical corrosion resistance and mechanical properties, and are difficult to meet complex environments and engineering needs.

Method used

The substrate layer is formed by cross-linking reaction of two-component polyurethane and epoxy resin, and the self-adhesive layer of polyacrylate-siloxane hybrid resin, a mucosa formed by cross-linking of polyvinyl alcohol and boric acid, as well as self-healing microcapsules containing titanium dioxide and polyurea-polyurethane shell layers, plasticizers and other components.

Benefits of technology

It significantly improves the weather resistance, self-adhesion, water resistance, chemical corrosion resistance and mechanical properties of the coil material, so that it maintains stability and applicability in extreme environments, extends its service life, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736026A_ABST
    Figure CN119736026A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of waterproof materials, and discloses a super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material, including a substrate layer, a self-adhesive layer, a sub-adhesive film, a self-repairing microcapsule and a plasticizer, wherein the substrate layer is formed by cross-linking a two-component polyurethane and an epoxy resin, and the total weight of the two-component polyurethane and the epoxy resin in the substrate layer accounts for 40%-60% of the total weight of the waterproofing coiled material, and also discloses a super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material preparation method, comprising the following steps: S1, preparing a substrate layer: mixing the two-component polyurethane and the epoxy resin in a weight ratio of 1:1, adding an amine catalyst, heating to 60-80°C and maintaining a cross-linking reaction for 30-60min. The mechanical strength and weather resistance are enhanced by cross-linking the substrate layer, the self-adhesive layer provides excellent adhesion, the sub-adhesive film is easy to peel off and has no residue, the self-repairing microcapsule prolongs the service life, and adopts environmentally friendly materials to achieve a balance between high performance and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waterproof materials, in particular to a super-weather-resistant strong self-adhesive polymer self-adhesive film waterproof coiled material and a preparation method thereof. Background Art

[0002] With the development of modern construction technology and the increasing demand for building durability, the role of waterproof membranes in building waterproof systems has become increasingly prominent. Waterproof membranes are a key material for protecting building structures from moisture damage. They are widely used in projects that require waterproofing and moisture-proofing, such as roofs, basements, tunnels, bridges, sewage treatment facilities, and chemical plants. Especially in the waterproofing of buildings that are exposed to the outdoors for a long time, waterproof membranes need to have excellent weather resistance, self-adhesion, waterproofness, chemical corrosion resistance, and mechanical properties to cope with the challenges of various complex environments. However, traditional waterproof membranes have many shortcomings in these aspects.

[0003] In the application of waterproofing membranes, common materials include PVC membranes, asphalt-based membranes and rubber membranes. Although these materials have certain waterproofing effects in specific environments, in actual applications, due to the limitations of the natural environment and construction conditions, their performance is often difficult to meet the increasingly complex engineering needs, and there are the following problems:

[0004] Insufficient weather resistance: Building waterproofing membranes are prone to aging when exposed to ultraviolet rays, high temperature and high humidity for a long time, resulting in a gradual decrease in waterproofing effect. Traditional PVC membranes and asphalt-based membranes will crack, powder and change color under continuous ultraviolet radiation. This degradation not only affects the aesthetics of the waterproof layer, but more importantly, it causes the physical properties of the membrane to deteriorate and shortens its service life. For waterproof membranes that have been used outdoors for a long time, insufficient weather resistance makes them unable to meet engineering requirements, and frequent replacement of the waterproof layer will also increase maintenance costs.

[0005] Poor self-adhesion and unsatisfactory construction effect: Traditional waterproofing membranes usually rely on additional adhesives or hot melt technology to achieve adhesion to the substrate. However, these additional construction processes result in poor adhesion of the membrane on smooth surfaces, especially on smooth substrates such as stainless steel and glass. In addition, the adhesive has low durability and is easily affected by environmental factors and aged, causing the membrane to fall off after long-term use, affecting the overall waterproofing effect. The inconvenience during the construction process also increases the difficulty of membrane construction, affecting the construction efficiency and the stability of the waterproof layer.

[0006] In order to solve the above-mentioned deficiencies in the performance of the existing coiled materials, the present invention proposes a super weather-resistant strong self-adhesive polymer self-adhesive film waterproof coiled material and a preparation method thereof. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides a super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material and a preparation method thereof, which solves the problems of the existing waterproofing coiled materials in terms of weather resistance, self-adhesion, waterproofness, chemical corrosion resistance and mechanical properties.

[0008] To achieve the above purpose, the present invention is implemented by the following technical scheme: a super weather-resistant strong self-adhesive polymer self-adhesive film waterproof coiled material, comprising a substrate layer, a self-adhesive layer, a sub-adhesive film, a self-repairing microcapsule and a plasticizer, wherein the substrate layer is formed by cross-linking a two-component polyurethane and an epoxy resin, and the total weight of the two-component polyurethane and the epoxy resin in the substrate layer accounts for 40%-60% of the total weight of the waterproof coiled material;

[0009] The self-adhesive layer is a polyacrylate-siloxane hybrid resin, and the self-adhesive layer accounts for 20%-30% of the total weight of the waterproof membrane;

[0010] The sub-adhesive film is formed by cross-linking polyvinyl alcohol and boric acid, and the sub-adhesive film accounts for 5%-10% of the total weight of the waterproofing membrane;

[0011] The self-repairing microcapsules account for 1%-3% of the total weight of the waterproof membrane;

[0012] The plasticizer accounts for 5%-10% of the total weight of the waterproof coiled material.

[0013] Preferably, the two-component polyurethane comprises an isocyanate-based component and a hydroxyl-containing polyol, and the cross-linking reaction between the two-component polyurethane and the epoxy resin in the substrate layer is carried out under the action of a catalyst, and the catalyst is an amine catalyst.

[0014] Preferably, the self-repairing capsule comprises titanium dioxide and a polyurea-polyurethane shell layer.

[0015] A method for preparing a super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material, which is used to prepare the super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material described above, comprises the following steps:

[0016] S1. Prepare the substrate layer: mix two-component polyurethane and epoxy resin in a weight ratio of 1:1, add an amine catalyst, heat to 60-80°C and keep for 30-60 minutes for cross-linking reaction, and cool to room temperature for use;

[0017] S2. preparing a self-adhesive layer: mixing polyacrylate and siloxane in a weight ratio of 1:1, performing a sol-gel reaction for 30-60 minutes at a pH value of 4-6 and a temperature of 40-50° C. to form an organic-inorganic hybrid network, and coating the obtained self-adhesive layer on the substrate layer;

[0018] S3. Preparing a mucoadhesive film: mixing polyvinyl alcohol and boric acid, reacting for 10-20 minutes at room temperature to form a borate bond with a dynamic cross-linking structure, and coating the obtained mucoadhesive film on the self-adhesive layer;

[0019] S4, adding self-repairing microcapsules: evenly dispersing the self-repairing microcapsules in the substrate layer;

[0020] S5. Add plasticizer: Add aliphatic polyamide and amine crosslinking agent to the substrate layer, the curing temperature is 80-100℃, and the curing time is 30-45min

[0021] Preferably, the step S1 of preparing the substrate layer specifically comprises the following steps:

[0022] S1.1, Raw material preparation: weigh the isocyanate component and the hydroxyl-containing polyol component in the two-component polyurethane, mix them in a weight ratio of 1:1, weigh the epoxy resin in proportion, so that the total weight of the two-component polyurethane and the epoxy resin accounts for 40%-60% of the total weight of the waterproof membrane;

[0023] S1.2, catalyst addition: add amine catalyst, accounting for 0.1%-1% of the total weight, and stir evenly;

[0024] S1.3, heating and cross-linking reaction: heat the mixture to 60-80°C and maintain for 30-60 minutes;

[0025] S1.4, Reaction process: Isocyanate groups react with hydroxyl groups of polyols to form urea bonds, epoxy groups open the ring, and cross-link with hydroxyl groups of polyurethane;

[0026] S1.5. Cooling: After the reaction is completed, the substrate layer is cooled to room temperature.

[0027] Preferably, the preparation of the self-adhesive layer in step S2 specifically comprises the following steps:

[0028] S2.1. Raw material preparation: Weigh polyacrylate and amino-containing silicone in a weight ratio of 1:1, so that the total weight of the self-adhesive layer accounts for 20%-30% of the total weight of the waterproof membrane;

[0029] S2.2, pH and temperature control: Use buffer solution to adjust the pH value of the solution to 4-6 and heat to 40-50℃;

[0030] S2.3, sol-gel reaction: under the temperature and pH conditions, polyacrylate and siloxane undergo a sol-gel reaction to form an organic-inorganic hybrid network structure, during which the hydroxyl groups in the siloxane molecules condense to form Si-O-Si bonds, and cross-link with the acrylate groups through covalent bonds and hydrogen bonds;

[0031] S2.4, stirring and reaction time: the reaction time is controlled at 30-60min, and stirring is performed;

[0032] S2.5, coating: evenly coating the formed self-adhesive layer on the cooled substrate layer.

[0033] Preferably, the preparation of the mucosa in step S3 specifically comprises the following steps:

[0034] S3.1. Raw material preparation: weigh polyvinyl alcohol and boric acid in proportion so that the total weight of the sub-adhesive film accounts for 5%-10% of the total weight of the waterproof membrane, of which the proportion of polyvinyl alcohol is 3%-5% and the proportion of boric acid is 2%-5%;

[0035] S3.2, mixing and dissolving: dissolving polyvinyl alcohol and boric acid in water and stirring evenly;

[0036] S3.3, cross-linking reaction: stirring at room temperature for 10-20 minutes to allow the hydroxyl groups of the polyvinyl alcohol to undergo a cross-linking reaction with the boric acid to form a cross-linking structure of borate ester bonds;

[0037] S3.4, coating: evenly coating the self-adhesive film formed by the reaction on the surface of the self-adhesive layer.

[0038] Preferably, the step S4 of adding the self-repairing microcapsules specifically comprises the following steps:

[0039] S4.1. Raw material preparation and dispersion: weigh the self-repairing microcapsules according to 1%-3% of the total weight of the waterproof membrane;

[0040] S4.2, uniform dispersion: the self-healing microcapsules are uniformly dispersed in the substrate layer, using a low speed of 300-500 rpm stirring;

[0041] S4.3, Microcapsule reaction process: Titanium dioxide generates free radicals under ultraviolet light, which trigger the rupture of the polyurea-polyurethane shell of the microcapsule and release the internal repair agent.

[0042] Preferably, the step S5 specifically includes the following steps:

[0043] S5.1. Raw material preparation: weigh aliphatic polyamide and amine crosslinking agent according to 5%-10% of the total weight of the waterproof membrane, of which aliphatic polyamide accounts for 3%-7% and amine crosslinking agent accounts for 2%-3%;

[0044] S5.2, mixing and dispersing: adding aliphatic polyamide and amine crosslinking agent into the substrate layer and stirring evenly;

[0045] S5.3, curing and cross-linking reaction: heat the mixture to 80-100°C, maintain for 30-45 minutes, and perform cross-linking reaction;

[0046] S5.4. Cooling: After curing is completed, cool the waterproof membrane to room temperature.

[0047] Preferably, the amine catalyst in step S1.2 is optionally one of triethylamine or diethyltoluidine.

[0048] The invention provides a super weather-resistant strong self-adhesive polymer self-adhesive film waterproof coiled material and a preparation method thereof.

[0049] It has the following beneficial effects:

[0050] 1. The present invention forms a stable three-dimensional network structure by adopting a cross-linking reaction of two-component polyurethane and epoxy resin. The network structure provides stronger connection and support at the molecular level, so that the material has better tensile and impact resistance under the action of external force. At the same time, the three-dimensional cross-linked network structure improves the density and stability of the material, making it difficult to decompose or degrade under ultraviolet radiation and high temperature and high humidity environments, thereby having excellent weather resistance, enabling the substrate layer to maintain a high stability in extreme environments, reducing the aging rate of the material under harsh conditions such as high temperature, ultraviolet rays and humidity changes, and being suitable for long-term outdoor use.

[0051] 2. The self-adhesive layer prepared by the sol-gel reaction of polyacrylate and siloxane in the present invention forms an organic-inorganic hybrid network structure. The hybrid structure combines the flexibility of organic polyacrylate and the hardness of inorganic siloxane to provide excellent adhesion. The inorganic siloxane part enhances weather resistance and heat resistance, while the organic polyacrylate provides good adhesion and flexibility, so that the self-adhesive layer can still maintain stable adhesion performance under high temperature and high humidity environment, and can be firmly attached to the surface of various substrates. The self-adhesive layer not only has excellent adhesion performance, but also can maintain stable adhesion under high humidity and high temperature environment, thereby improving the applicability of the product.

[0052] 3. The self-adhesive film of the present invention adopts the cross-linking of polyvinyl alcohol and boric acid to form a dynamic borate bond structure, which is reversible and can be broken and recombined under the action of external force. The dynamic cross-linking structure gives the self-adhesive film the characteristic of easy peeling. No residual glue will be left when peeling, and the integrity of the self-adhesive layer will not be damaged. This design greatly simplifies the construction process and reduces the cleaning work. At the same time, it ensures the cleanliness of the surface of the coil and achieves an excellent self-adhesive effect, avoiding the problem of residue in actual application, which helps to improve the convenience of construction and the overall aesthetics.

[0053] 4. The present invention can achieve automatic repair of microcracks under ultraviolet irradiation by adding self-repairing microcapsules containing titanium dioxide and polyurea-polyurethane shell layers into the substrate layer. Titanium dioxide generates free radicals under ultraviolet irradiation, and the free radicals trigger the rupture of the microcapsule shell layer and release the internal repair agent, thereby filling the microcracks in the substrate layer. This self-repair mechanism enables the material to automatically heal tiny damages under long-term outdoor exposure, reduces the possibility of crack expansion, reduces the risk of failure caused by microcracks, and extends the overall service life of the material.

[0054] 5. The present invention reduces environmental pollution by adopting polyurethane, siloxane and plasticizer materials with low VOC content. At the same time, the PVA / boric acid cross-linking structure in the sub-mucosal membrane forms a borate bond, which is a dynamic cross-linking bond that is more easily broken in the natural environment. The reversibility and weakening effect of the borate bond enable the sub-mucosal membrane to be decomposed into small molecules under the action of moisture, microorganisms or other environmental factors. These small molecules are easily decomposed by microorganisms in nature, thereby avoiding persistent pollution to the environment. Therefore, the combination of PVA and boric acid gives the sub-mucosal membrane good degradability, while meeting the requirements of environmentally friendly design, and can reduce the environmental burden during construction and use, so that the waterproof membrane product of the present invention achieves a good balance in performance and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION

[0056] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0057] Please see attached Figure 1 The embodiment of the present invention provides a super weather-resistant strong self-adhesive polymer self-adhesive film waterproof roll, including a substrate layer, a self-adhesive layer, a sub-adhesive film, a self-repairing microcapsule and a plasticizer. The substrate layer is formed by cross-linking a two-component polyurethane and an epoxy resin, and the total weight of the two-component polyurethane and the epoxy resin in the substrate layer accounts for 40%-60% of the total weight of the waterproof roll; the self-adhesive layer is a polyacrylate-silicone hybrid resin, and the self-adhesive layer accounts for 20%-30% of the total weight of the waterproof roll; the sub-adhesive film is formed by cross-linking polyvinyl alcohol and boric acid, and the sub-adhesive film accounts for 5%-10% of the total weight of the waterproof roll; the self-repairing microcapsule accounts for 1%-3% of the total weight of the waterproof roll; the plasticizer accounts for 5%-10% of the total weight of the waterproof roll.

[0058] The two-component polyurethane comprises an isocyanate component and a hydroxyl-containing polyol, and the cross-linking reaction of the two-component polyurethane and the epoxy resin in the substrate layer is carried out under the action of a catalyst, which is an amine catalyst. The self-repairing capsule comprises titanium dioxide and a polyurea-polyurethane shell layer.

[0059] A method for preparing a super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material, which is used to prepare a super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material, comprising the following steps:

[0060] S1. Prepare the substrate layer: mix two-component polyurethane and epoxy resin in a weight ratio of 1:1, add an amine catalyst, heat to 60-80°C and keep for 30-60 minutes for cross-linking reaction, and cool to room temperature for use;

[0061] S2. preparing a self-adhesive layer: mixing polyacrylate and siloxane in a weight ratio of 1:1, performing a sol-gel reaction for 30-60 minutes at a pH value of 4-6 and a temperature of 40-50° C. to form an organic-inorganic hybrid network, and coating the obtained self-adhesive layer on the substrate layer;

[0062] S3. Preparing a mucoadhesive film: mixing polyvinyl alcohol and boric acid, reacting for 10-20 minutes at room temperature to form a borate bond with a dynamic cross-linking structure, and coating the obtained mucoadhesive film on the self-adhesive layer;

[0063] S4, adding self-repairing microcapsules: evenly dispersing the self-repairing microcapsules in the substrate layer;

[0064] S5. Adding plasticizer: Add aliphatic polyamide and amine cross-linking agent to the substrate layer, with a curing temperature of 80-100°C and a curing time of 30-45 minutes.

[0065] Step S1: preparing the substrate layer specifically comprises the following steps:

[0066] S1.1, Raw material preparation: weigh the isocyanate component and the hydroxyl-containing polyol component in the two-component polyurethane, mix them in a weight ratio of 1:1, weigh the epoxy resin in proportion, so that the total weight of the two-component polyurethane and the epoxy resin accounts for 40%-60% of the total weight of the waterproof membrane;

[0067] S1.2, catalyst addition: add amine catalyst, accounting for 0.1%-1% of the total weight, and stir evenly;

[0068] S1.3, heating and cross-linking reaction: heat the mixture to 60-80°C and maintain for 30-60 minutes;

[0069] S1.4, reaction process:

[0070] The isocyanate group (-NCO) reacts with the hydroxyl group (-OH) of the polyol to form a urea bond (-NHCOO-);

[0071] The epoxy group (-COC-) ring opens and cross-links with the hydroxyl group of the polyurethane;

[0072] Chemical reaction formula: R-NCO+R′-OH→R-NH-COO-R

[0073] Epoxy resin + hydroxyl → cross-linked structure

[0074] S1.5. Cooling: After the reaction is completed, the substrate layer is cooled to room temperature.

[0075] Step S2 of preparing the self-adhesive layer specifically comprises the following steps:

[0076] S2.1. Raw material preparation: Weigh polyacrylate and amino-containing silicone in a weight ratio of 1:1, so that the total weight of the self-adhesive layer accounts for 20%-30% of the total weight of the waterproof membrane;

[0077] S2.2, pH and temperature control: Use buffer solution to adjust the pH value of the solution to 4-6 and heat to 40-50℃;

[0078] S2.3, sol-gel reaction: under temperature and pH conditions, polyacrylate and siloxane undergo sol-gel reaction to form an organic-inorganic hybrid network structure. During the reaction, the hydroxyl groups in the siloxane molecules condense to form Si-O-Si bonds, which are cross-linked with the acrylate groups through covalent bonds and hydrogen bonds.

[0079] Chemical reaction formula: Si-OH+Si-OH→Si-O-Si+H2O

[0080] S2.4, stirring and reaction time: the reaction time is controlled at 30-60min, and stirring is performed;

[0081] S2.5, coating: evenly coating the formed self-adhesive layer on the cooled substrate layer.

[0082] Step S3 of preparing the mucosa specifically comprises the following steps:

[0083] S3.1. Raw material preparation: weigh polyvinyl alcohol and boric acid in proportion so that the total weight of the sub-adhesive film accounts for 5%-10% of the total weight of the waterproof membrane, of which the proportion of polyvinyl alcohol is 3%-5% and the proportion of boric acid is 2%-5%;

[0084] S3.2, mixing and dissolving: dissolving polyvinyl alcohol and boric acid in water and stirring evenly;

[0085] S3.3, cross-linking reaction: stirring at room temperature for 10-20 minutes to allow the hydroxyl groups of the polyvinyl alcohol to undergo a cross-linking reaction with the boric acid to form a cross-linking structure of borate ester bonds;

[0086] Principle of cross-linking reaction: Polyvinyl alcohol molecules contain hydroxyl groups (-OH), and boric acid molecules can react with these hydroxyl groups to form borate ester bonds. Specifically, boric acid (B(OH)3) forms a covalent bond with the hydroxyl groups of PVA, and forms a borate ester bond through dehydration. This process forms a three-dimensional cross-linked network between molecules, thereby increasing the strength and adhesion of the material.

[0087] Chemical reaction formula: The hydroxyl group of polyvinyl alcohol (PVA) reacts with boric acid to form a borate ester bond.

[0088] The simplified reaction equation is as follows:

[0089] PVA-OH+B(OH)3→PVA-OB(OH)2+H2O

[0090] Multiple PVA chains are further cross-linked with boric acid to form a cross-linked network structure:

[0091] PVA-OH+B(OH)3+PVA-OH→PVA-OBO-PVA+2H2O

[0092] The cross-linked structure connects multiple PVA molecular chains together through borate bonds, ultimately forming a cross-linked network of the mucosa.

[0093] S3.4, coating: evenly coating the self-adhesive film formed by the reaction on the surface of the self-adhesive layer.

[0094] The step S4 of adding self-repairing microcapsules specifically includes the following steps:

[0095] S4.1. Raw material preparation and dispersion: weigh the self-repairing microcapsules according to 1%-3% of the total weight of the waterproof membrane;

[0096] S4.2, uniform dispersion: the self-healing microcapsules are uniformly dispersed in the substrate layer, using a low speed of 300-500 rpm stirring;

[0097] S4.3, Microcapsule reaction process: Titanium dioxide generates free radicals under ultraviolet light, which trigger the rupture of the polyurea-polyurethane shell of the microcapsule and release the internal repair agent.

[0098] Step S5 specifically includes the following steps:

[0099] S5.1. Raw material preparation: weigh aliphatic polyamide and amine crosslinking agent according to 5%-10% of the total weight of the waterproof membrane, of which aliphatic polyamide accounts for 3%-7% and amine crosslinking agent accounts for 2%-3%;

[0100] S5.2, mixing and dispersing: adding aliphatic polyamide and amine crosslinking agent into the substrate layer and stirring evenly;

[0101] S5.3, curing and cross-linking reaction: heat the mixture to 80-100°C, maintain for 30-45 minutes, and perform cross-linking reaction;

[0102] Chemical reaction formula: R-CONH-R′+R”-NH2→cross-linked structure

[0103] S5.4. Cooling: After curing is completed, the waterproof membrane is cooled.

[0104] In step S1.2, the amine catalyst can be any one of triethylamine and diethyltoluidine.

[0105] Example 1

[0106] Substrate layer preparation:

[0107] Raw material preparation: Weigh 50 grams each of the two-component polyurethane isocyanate component and the polyol component, mix them in a 1:1 weight ratio, add 50 grams of epoxy resin, and make the substrate layer account for 50% of the total weight.

[0108] Catalyst addition: Add 0.5 g of triethylamine and stir well.

[0109] Heating and cross-linking reaction: Heat to 70°C and maintain for 45 minutes.

[0110] Cooling: After the reaction is completed, cool to room temperature.

[0111] Self-adhesive layer preparation:

[0112] Raw material preparation: Weigh 25 grams each of polyacrylate and amino-containing silicone, and mix them in a weight ratio of 1:1 so that the self-adhesive layer accounts for 25% of the total weight.

[0113] pH and temperature control: Adjust pH to 5 and heat to 45°C.

[0114] Sol-gel reaction: react at 45°C and pH 5 for 45 minutes.

[0115] Coating: Evenly coat the self-adhesive layer on the substrate layer.

[0116] Submucosal preparation:

[0117] Raw material preparation: Weigh 4 grams of polyvinyl alcohol and 3 grams of boric acid so that the mucosa accounts for 7% of the total weight.

[0118] Mixing and dissolving: Dissolve in appropriate amount of water and stir well.

[0119] Cross-linking reaction: Stir at room temperature for 15 minutes.

[0120] Coating: Evenly coat the adhesive film on the self-adhesive layer.

[0121] Self-healing microcapsules: Raw material preparation and dispersion: Weigh 2 grams of self-healing microcapsules, evenly disperse them in the substrate layer, and stir at 300 rpm.

[0122] Microcapsule reaction: Free radicals are generated under ultraviolet irradiation.

[0123] Plasticizer:

[0124] Raw material preparation: weigh 6 grams of aliphatic polyamide and 3 grams of amine cross-linking agent so that the plasticizer accounts for 9% of the total weight.

[0125] Mixing and dispersing: Add aliphatic polyamide and amine crosslinking agent into the substrate layer and stir evenly.

[0126] Curing and cross-linking reaction: Heat to 90°C and keep for 40 minutes.

[0127] Cooling: Cool to room temperature after curing is complete.

[0128] Summary: This example achieves the basic performance of a super-weather-resistant strong self-adhesive membrane waterproofing roll through basic parameter settings. The base material layer uses a 1:1 ratio of two-component polyurethane and epoxy resin to provide stable mechanical strength and weather resistance; the self-adhesive layer's polyacrylate and silicone are mixed in a 1:1 ratio, so that the adhesion performance shows good initial adhesion and lasting adhesion on a variety of substrates; the addition of the membrane and self-repairing microcapsules ensures easy peeling and automatic repair capabilities. This basic formula provides a reference benchmark for subsequent optimization.

[0129] Example 2

[0130] Substrate layer: 52g of isocyanate component and polyol component, 52g of epoxy resin, the total weight accounts for 52% of the total weight of the waterproof membrane. The catalyst uses diethyltoluidine, 0.6g. The heating temperature is 72℃, and it is maintained for 50 minutes.

[0131] Self-adhesive layer: 26g of polyacrylate and 26g of amino-containing siloxane, the total weight of the self-adhesive layer accounts for 26%. pH 5.2, temperature 47°C. Sol-gel reaction for 50 minutes.

[0132] Mucosa: 4.2 g polyvinyl alcohol, 3.5 g boric acid, total weight of mucosa accounts for 7.7%. Reaction at room temperature for 17 minutes.

[0133] Self-healing microcapsules: 2.1 g of self-healing microcapsules were evenly dispersed in the substrate layer and stirred at 350 rpm.

[0134] Plasticizer: 6.3 g aliphatic polyamide, 3.2 g amine crosslinker, total weight of plasticizer is 9.5%. Curing temperature is 92°C, hold for 42 minutes.

[0135] Summary: Based on Example 1, this example fine-tunes the proportion of each component and the reaction parameters to improve the interlayer bonding and overall stability of the coiled material. The amount of isocyanate-based components and epoxy resins in the substrate layer is slightly increased to 52 grams, and the total proportion is increased to 52%, which slightly improves the thickness and mechanical properties of the substrate layer; diethyltoluidine is used as a catalyst, and the amount is increased to 0.6 grams, which enhances the uniformity of the cross-linking reaction, thereby improving the strength and stability of the material. At the same time, the temperature and reaction time of the self-adhesive layer are also improved, which effectively improves the adhesion of the coiled material on a variety of substrates. Overall, Example 2 is slightly better than Example 1 in basic performance and is suitable for applications requiring higher adhesion and structural stability.

[0136] Example 3

[0137] Substrate layer: 53g of isocyanate component and polyol component, 53g of epoxy resin, the total weight accounts for 53% of the total weight of the waterproof membrane. The catalyst uses triethylamine, 0.7g. The heating temperature is 75℃, and it is maintained for 55 minutes.

[0138] Self-adhesive layer: 27 g of polyacrylate and 27 g of amino-containing silicone, the total weight of the self-adhesive layer accounts for 27%. pH 5.5, temperature 48°C. Sol-gel reaction for 55 minutes.

[0139] Mucosa: 4.5 g polyvinyl alcohol, 3.7 g boric acid, 8.2% of the total weight of mucosa. Reaction at room temperature for 18 minutes.

[0140] Self-healing microcapsules: 2.2 g of self-healing microcapsules were evenly dispersed in the substrate layer and stirred at 400 rpm.

[0141] Plasticizer: 6.5g aliphatic polyamide, 3.5g amine crosslinker, total weight of plasticizer is 10%. Curing temperature is 95℃, keep for 45 minutes.

[0142] Summary: Based on Example 2, this example further optimizes the amount of catalyst and the heating temperature to make the cross-linking reaction more uniform, thereby achieving a more stable three-dimensional cross-linking structure. The amount of catalyst in the substrate layer is increased to 0.7 grams, and the heating temperature is increased to 75°C and maintained for 55 minutes, so that the hardness and toughness of the substrate layer are better; the ratio of polyacrylate and amino-containing siloxane in the self-adhesive layer is slightly increased to 27%, which improves the thickness and stability of the self-adhesive layer. These adjustments enhance the mechanical properties of the coiled material, especially in harsh environments such as high humidity and high temperature. Therefore, Example 3 has better structural stability and anti-aging ability than the previous two examples, and is suitable for more harsh environments.

[0143] Example 4

[0144] Substrate layer: 54 g of isocyanate component and polyol component, 54 g of epoxy resin, total weight accounts for 54%. Catalyst uses diethyltoluidine, 0.75 g. Heating temperature is 78°C, maintained for 60 minutes.

[0145] Self-adhesive layer: 28g of polyacrylate and 28g of amino-containing siloxane, the total weight of the self-adhesive layer accounts for 28%. pH 5.7, temperature 49°C. Sol-gel reaction for 60 minutes.

[0146] Mucosa: 4.8g polyvinyl alcohol, 4g boric acid, total weight of mucosa accounts for 8.8%. Reaction at room temperature for 19 minutes.

[0147] Self-healing microcapsules: 2.5 g of self-healing microcapsules were evenly dispersed in the substrate layer and stirred at 450 rpm.

[0148] Plasticizer: 6.8g aliphatic polyamide, 3.2g amine crosslinker, total weight of plasticizer is 10%. Curing temperature is 98℃, keep for 45 minutes.

[0149] Summary: Compared with Example 3, this example further improves the reaction time, temperature and catalyst dosage, so that the structural stability and uniformity of the material reach a higher level. The dosage of isocyanate and epoxy resin in the substrate layer is further increased, the catalyst usage also reaches 0.75 grams, the cross-linking temperature is increased to 78°C, and the reaction time is extended to 60 minutes. These adjustments ensure higher hardness and UV resistance of the substrate layer. The sol-gel reaction conditions of the self-adhesive layer have been optimized, the pH is increased to 5.7, the temperature is adjusted to 49°C, and the reaction time is 60 minutes, which makes the hybrid network structure of the self-adhesive layer more stable and improves the adhesion strength and weather resistance. Overall, Example 4 has better bonding strength and durability, and is particularly suitable for scenarios with extremely high requirements for adhesion and environmental tolerance.

[0150] Example 5

[0151] Substrate layer: 55g of isocyanate component and polyol component, 55g of epoxy resin, total weight accounts for 55%. Catalyst uses triethylamine, 0.8g. Heating temperature is 80℃, maintained for 60 minutes.

[0152] Self-adhesive layer: 30 g each of polyacrylate and amino-containing silicone, the total weight of the self-adhesive layer accounts for 30%. pH 6.0, temperature 50°C. Sol-gel reaction for 60 minutes.

[0153] Mucosa: 5g polyvinyl alcohol, 4.5g boric acid, 9.5% of the total weight of mucosa. React at room temperature for 20 minutes.

[0154] Self-healing microcapsules: 3 g of self-healing microcapsules were evenly dispersed in the substrate layer and stirred at 500 rpm.

[0155] Plasticizer: 7g aliphatic polyamide, 3g amine crosslinker, total weight of plasticizer is 10%. Curing temperature is 100℃, keep for 45 minutes.

[0156] Summary: Based on Example 4, this embodiment further increases key parameters such as the amount of catalyst and the reaction temperature, and realizes the optimization of the coil material structure. The isocyanate component and polyol component of the substrate layer are both increased to 55 grams, and the total proportion is increased to 55%; the amount of catalyst triethylamine is increased to 0.8 grams, the heating temperature reaches 80°C, and it is maintained for 60 minutes, so that the cross-linking reaction of the substrate layer is sufficient, and the structure is more compact, thereby greatly improving the mechanical strength. The proportion of polyacrylate and amino-containing siloxane in the self-adhesive layer is increased to 30%, and the reaction is carried out at pH 6.0 and 50°C for 60 minutes, and the adhesion performance and environmental resistance of the self-adhesive layer are further optimized. The amount of sub-mucosal and self-repairing microcapsules is also increased accordingly to adapt to the overall material structure with higher performance requirements. Therefore, Example 5 is the most optimized solution, with the highest mechanical strength, best adhesion and longest service life, and is particularly suitable for high-demand outdoor waterproof engineering applications.

[0157] Experimental design:

[0158] Experiment 1: Weathering Test

[0159] Experimental purpose: To verify the weather resistance of the coiled material of the present invention under ultraviolet irradiation, high temperature and high humidity environment, and to evaluate its anti-aging performance in long-term outdoor applications. This experiment focuses on observing whether the material can maintain structural stability in ultraviolet and high humidity environments, thereby verifying the innovative role of the material components of the present invention.

[0160] Experimental preparation:

[0161] Experimental materials: roll material samples of Examples 1 to 5; traditional roll material A (PVC roll material); traditional roll material B (asphalt-based waterproof roll material).

[0162] Experimental equipment: UV aging test chamber (to control temperature and humidity); temperature and humidity control equipment (set to 60°C, 85% humidity); colorimeter (for measuring color change); microscope (for observing crack density).

[0163] Experimental steps:

[0164] Sample cutting and marking:

[0165] Cut each coil into 5cmx5cm samples, prepare 5 groups of samples, 3 pieces in each group, for 100 hours, 200 hours, 300 hours, 400 hours and 500 hours of stage tests. Mark the corresponding time point and number on the back of each sample.

[0166] Place samples: Place all samples flatly on the sample rack of the UV aging test chamber, ensuring that there is no overlap between samples to facilitate uniform exposure to UV rays.

[0167] Start the experiment: Set the environmental conditions of the UV aging test chamber: temperature 60℃, humidity 85%, UV intensity 0.76W / m 2 . Start the test chamber and ensure that the equipment operates continuously under the set conditions.

[0168] Phased testing:

[0169] Every 100 hours, close the test chamber and take out the samples at the corresponding time points, and observe and measure according to the following steps:

[0170] Surface aging detection: observe the powdering, cracking, peeling and other phenomena with the naked eye, and observe the crack density (number of cracks per square centimeter) with a microscope.

[0171] Color difference measurement: Use a colorimeter to measure the color difference of each sample and record the △E value.

[0172] Material integrity check: Subjectively judge the overall structural integrity of the sample and record it as "complete", "slightly powdered", "many cracks", etc.

[0173] Record and analyze: Record the observed data at each time point in a table. After the observation is completed, put the remaining samples back into the test chamber and continue the test at the next time point.

[0174] Clean the equipment: After the experiment, close the test chamber and clean the residue inside to ensure that the equipment can be used normally for the next experiment.

[0175] Table 1:

[0176]

[0177]

[0178]

[0179] Result analysis: The coil of the present invention exhibits excellent weather resistance after 500 hours of ultraviolet irradiation, without obvious powdering and cracking, while the traditional coils A and B show powdering and cracking after 200 hours. This is attributed to the cross-linked structure of the two-component polyurethane and epoxy resin in the substrate layer, which increases the stability and UV resistance of the substrate. The color difference of the coil of the present invention changes slightly (△E<0.7), while the color difference values ​​of the traditional coils A and B exceed 3.5 after 500 hours, indicating that the component combination of the coil of the present invention effectively reduces the color change of the material under ultraviolet irradiation. Throughout the test, the crack density of Examples 1 to 5 was zero, while the crack density of the traditional coils A and B increased significantly over time. This shows that the cross-linked structure of the two-component polyurethane and epoxy resin effectively prevents the generation of cracks in a high ultraviolet environment, showing excellent anti-aging performance.

[0180] Experiment 2: Self-adhesion test

[0181] Experimental purpose: To evaluate the adhesion performance (initial adhesion and sustained adhesion) of the coiled material of the present invention on different substrates (stainless steel and glass) and to verify the adhesion effect of the self-adhesive layer (polyacrylate-siloxane hybrid resin).

[0182] Experimental preparation:

[0183] Experimental materials: coil samples of Examples 1 to 5; conventional coil A and conventional coil B; stainless steel plates and glass plates.

[0184] Experimental equipment: Initial adhesion tester (accurate to 0.01N / cm 2 ); Adhesion test device (with 500 g standard weight); Temperature and humidity control equipment (set to 23° C., 50% humidity).

[0185] Experimental steps:

[0186] Sample cutting and preparation: Cut each coil into 2cmx10cm strips for testing stainless steel plates and glass plates respectively. Prepare 3 pieces of each sample to ensure the accuracy of the data.

[0187] Environmental settings: Control the laboratory environment temperature at 23°C and humidity at 50%. Leave the sample for 30 minutes to ensure the temperature and humidity balance between the sample and the experimental environment.

[0188] Initial adhesion test:

[0189] Stainless steel plate: Attach the sample to the stainless steel plate and apply 2N / cm2 on the sample surface using an initial adhesion tester. 2 Apply pressure, hold for 3 seconds, and record the initial adhesion value.

[0190] Glass plate: Attach the sample to a glass plate, repeat the above steps, and record the initial adhesion on the glass substrate.

[0191] Adhesion test:

[0192] Stainless steel plate: stick the sample vertically to the stainless steel plate, hang a 500g standard weight at the lower end, and observe the adhesion after 1 hour.

[0193] Glass plate: adhere the sample vertically to the glass plate, repeat the steps and record the holding force data.

[0194] Table 2:

[0195]

[0196]

[0197] Result analysis: The initial adhesion of Examples 1 to 5 is higher than 0.8 N / cm 2 The initial adhesion of traditional coils is low. The polyacrylate-siloxane hybrid resin used in the self-adhesive layer gives the material high adhesion and can adapt to different substrate surfaces. The coil of the present invention has excellent adhesion, and the adhesion on stainless steel and glass surfaces exceeds 0.6N / cm 2 The adhesion of the traditional roll is lower than this standard, which shows that the self-adhesive layer of the roll of the present invention has the ability to maintain adhesion in a variety of construction environments.

[0198] Experiment 3: Waterproof performance test

[0199] Experimental purpose: To verify the waterproof performance of the roll material of the present invention under high water pressure conditions, to evaluate the contribution of the combination of the self-adhesive layer and the substrate layer to the waterproof effect, and to ensure its application value in waterproof engineering.

[0200] Experimental preparation:

[0201] Experimental materials: coil samples of Examples 1 to 5; conventional coil A and conventional coil B.

[0202] Experimental equipment: water pressure penetration test device (water pressure can be adjusted to 0.5MPa); moisture analyzer (accurate to 0.01g / m 2 ).

[0203] Experimental steps:

[0204] Sample cutting and marking: Cut each coil into 10cmx10cm samples, and prepare 3 samples for each sample for repeated testing to ensure the reliability of the experimental data.

[0205] Install the sample: Install the sample flatly in the water pressure penetration test device and seal the edges of the sample to prevent water from leaking from the edges of the sample.

[0206] Water pressure test: adjust the water pressure to 0.5MPa and maintain it for 1 hour. During this period, check the stability of the water pressure regularly to ensure that the water pressure is constant.

[0207] Water seepage measurement: After 1 hour, turn off the device, take out the sample, and measure the water seepage with a moisture analyzer, and record it as g / m 2 ·h.

[0208] Table 3:

[0209] sample <![CDATA[Water infiltration amount (g / m 2 ·h)]]> Waterproof level (1-5) Example 1 0.2 5 Example 2 0.1 5 Example 3 0.05 5 Example 4 0.02 5 Example 5 0.01 5 Traditional Coil A 1.0 3 Traditional Coil B 1.5 2

[0210] Result analysis: The water permeability of the coiled material of the present invention is extremely low (<0.2g / m 2 h), reaching the highest waterproof grade 5, while the traditional roll material has a large amount of water seepage and a low waterproof grade. This is due to the organic-inorganic hybrid network structure of the self-adhesive layer, which further enhances the waterproof performance of the material.

[0211] Experiment 4: Chemical corrosion resistance test

[0212] Experimental purpose: To evaluate the corrosion resistance of the coiled material of the present invention in acid, alkali and salt environments, and to verify the stability of the chemical resistance of the self-adhesive layer in various harsh environments.

[0213] Experimental preparation:

[0214] Experimental materials: coil samples of Examples 1 to 5; conventional coil A and conventional coil B; salt solution (5% NaCl), acid solution (pH=3 sulfuric acid), alkaline solution (pH=11 sodium hydroxide)

[0215] Experimental equipment: gravimetric analyzer (accurate to 0.001g).

[0216] Experimental steps:

[0217] Sample cutting and weighing: Cut each coil into 5cmx5cm size, weigh and record the initial weight.

[0218] Immersion treatment: Immerse the samples in salt, acid and alkali solutions respectively, ensuring that they are completely immersed. Immerse the samples in each solution for 24 hours to ensure that the experimental data is reliable.

[0219] Sample cleaning and drying: After taking out the sample, rinse the residual solution on the surface with distilled water, gently wipe it dry with non-woven cloth, and weigh it after the surface water is completely evaporated.

[0220] Weight change measurement: Weigh again using a gravimetric analyzer and record the percent weight change.

[0221] Table 4:

[0222]

[0223] Result analysis: In salt, acid and alkali solutions, the weight changes of Examples 1 to 5 of the coils of the present invention are all less than 0.2%, while the weight changes of traditional coils A and B are between 1.5% and 2.5%, and there is a significant weight increase in acidic and alkaline solutions, indicating that a more serious chemical reaction and water absorption phenomenon have occurred. The weight change of the coils of the present invention in each solution is significantly smaller than that of traditional coils, showing excellent corrosion resistance. After the coils of the present invention are immersed in salt, acid and alkali solutions for 24 hours, there is no trace of corrosion on the surface and the integrity is maintained; while traditional coils A and B show obvious corrosion phenomena in acidic and alkaline solutions, especially in alkaline environments, the surface of traditional coil B shows peeling and cracking phenomena. This further shows that the chemical stability of the coils of the present invention is better than that of traditional coils, and it can better resist chemical corrosion.

[0224] Experiment 5: Mechanical properties test (tensile strength and elongation)

[0225] Experimental purpose: To verify the tensile strength and elongation at break of the coiled material of the present invention and to ensure the stability of the mechanical properties of the material during use.

[0226] Experimental preparation:

[0227] Experimental materials: coil samples of Examples 1 to 5; conventional coil A and conventional coil B.

[0228] Experimental equipment: tensile tester (conforming to ASTM D882 standard).

[0229] Experimental steps:

[0230] Sample cutting: Each coil was cut into dumbbell-shaped specimens (width 25 mm, length 100 mm) that conformed to ASTM standards. Three pieces of each sample were prepared to ensure the reliability of the results.

[0231] Install the sample: Clamp the sample flatly in the clamp of the tensile tester to ensure that there are no wrinkles that may affect the experimental data.

[0232] Tensile test: Set the tensile tester speed to 50 mm / min, start the test, and record the tensile strength (MPa) and elongation at break (%) of the sample.

[0233] Table 5:

[0234] sample Tensile strength(MPa) Elongation at break (%) Example 1 12.5 120 Example 2 13.0 125 Example 3 14.2 130 Example 4 15.0 135 Example 5 15.5 140 Traditional Coil A 8.0 60 Traditional Coil B 9.5 70

[0235] Summary:

[0236] The coiled material of the present invention has been subjected to 500 hours of aging test under ultraviolet irradiation, high temperature and high humidity environment, and there is no obvious powdering and cracking on the surface, the color difference change (△E) is less than 0.7, and the crack density is zero. This is attributed to the cross-linked structure of the two-component polyurethane and epoxy resin in the substrate layer, which significantly improves the anti-aging ability of the coiled material. In contrast, the traditional coiled material will show powdering, cracking and obvious color change after 200 hours, and has poor weather resistance.

[0237] The initial adhesion of the coiled material of the present invention on stainless steel and glass substrates is higher than 0.8N / cm 2 , the holding force exceeds 0.6N / cm 2 , showing excellent adhesion performance. This is due to the organic-inorganic hybrid structure of polyacrylate-siloxane in the self-adhesive layer, which enables the material to have excellent self-adhesive effect on different substrate surfaces. The initial adhesion and lasting adhesion of traditional roll materials are lower than this standard, indicating that their stability and adhesion in actual construction are insufficient.

[0238] Under a water pressure of 0.5 MPa, the water penetration of the coiled material of the present invention is less than 0.2 g / m 2 h, reaching the highest waterproof level (level 5), which is significantly better than the waterproofness of traditional rolls. The self-adhesive layer and the base material layer of the roll of the present invention together form a waterproof barrier, effectively preventing water penetration, and are suitable for use in high water pressure environments.

[0239] The coiled material of the present invention exhibits excellent corrosion resistance in acid, alkali and salt environments, with weight changes of less than 0.2% and no signs of corrosion on the surface. This excellent chemical resistance is mainly attributed to the self-adhesive layer of the polyacrylate-siloxane hybrid structure, in which the siloxane groups give the material high resistance to chemical corrosion, while traditional coiled materials show obvious corrosion in acid and alkali solutions and are difficult to use for a long time in corrosive environments.

[0240] The tensile strength of the coiled material of the present invention is between 12.5-15.5MPa, and the elongation at break is between 120%-140%, both of which are significantly better than traditional coiled materials. This shows that the coiled material of the present invention has higher fracture resistance and ductility under tensile stress, and can maintain mechanical stability in complex environments. The cross-linked structure of the two-component polyurethane and epoxy resin enhances the strength and flexibility of the material, making the coiled material more suitable for application scenarios that require durability and ductility.

[0241] Overall conclusion: The coiled material of the present invention shows significant improvement in the five key performance indicators of weather resistance, self-adhesion, waterproofness, chemical corrosion resistance and mechanical properties. The experimental data verifies that its innovation in material composition and structural design effectively enhances the comprehensive performance of the material. Compared with traditional PVC coiled materials and asphalt-based coiled materials, the coiled materials of the present invention have higher stability and adaptability in various extreme environments, meeting the needs of long-term application in harsh outdoor environments. This makes the coiled materials of the present invention have broad application potential and market prospects in building waterproofing, outdoor facility protection, chemical corrosion environment application, etc. The experimental results provide a solid theoretical basis and data support for the reliability of the coiled materials of the present invention in practical applications.

[0242] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A super weather-resistant self-adhesive polymer self-adhesive film waterproofing coiled material, comprising a substrate layer, a self-adhesive layer, a sub-adhesive film, a self-repairing microcapsule and a plasticizer, characterized in that: The substrate layer is formed by cross-linking two-component polyurethane and epoxy resin, and the total weight of the two-component polyurethane and epoxy resin in the substrate layer accounts for 40%-60% of the total weight of the waterproof coiled material; The self-adhesive layer is a polyacrylate-siloxane hybrid resin, and the self-adhesive layer accounts for 20%-30% of the total weight of the waterproof membrane; The sub-adhesive film is formed by cross-linking polyvinyl alcohol and boric acid, and the sub-adhesive film accounts for 5%-10% of the total weight of the waterproofing membrane; The self-repairing microcapsules account for 1%-3% of the total weight of the waterproof membrane; The plasticizer accounts for 5%-10% of the total weight of the waterproof coiled material.

2. The super weather-resistant self-adhesive polymer self-adhesive film waterproofing coiled material according to claim 1, characterized in that: The two-component polyurethane comprises an isocyanate component and a hydroxyl-containing polyol. The cross-linking reaction between the two-component polyurethane and the epoxy resin in the substrate layer is carried out under the action of a catalyst, and the catalyst is an amine catalyst.

3. The super weather-resistant self-adhesive polymer self-adhesive film waterproofing coiled material according to claim 1, characterized in that: The self-repairing capsule comprises titanium dioxide and a polyurea-polyurethane shell layer.

4. A method for preparing a super weather-resistant self-adhesive polymer self-adhesive film waterproofing coiled material, characterized in that: The method for preparing the super weather-resistant self-adhesive polymer self-adhesive film waterproofing coiled material according to any one of claims 1 to 3 comprises the following steps: S1. Prepare the substrate layer: mix two-component polyurethane and epoxy resin in a weight ratio of 1:1, add an amine catalyst, heat to 60-80°C and keep for 30-60 minutes for cross-linking reaction, and cool to room temperature for use; S2. preparing a self-adhesive layer: mixing polyacrylate and siloxane in a weight ratio of 1:1, performing a sol-gel reaction for 30-60 minutes at a pH value of 4-6 and a temperature of 40-50° C. to form an organic-inorganic hybrid network, and coating the obtained self-adhesive layer on the substrate layer; S3. Preparing a mucoadhesive film: mixing polyvinyl alcohol and boric acid, reacting for 10-20 minutes at room temperature to form a borate bond with a dynamic cross-linking structure, and coating the obtained mucoadhesive film on the self-adhesive layer; S4, adding self-repairing microcapsules: evenly dispersing the self-repairing microcapsules in the substrate layer; S5. Adding plasticizer: Add aliphatic polyamide and amine cross-linking agent to the substrate layer, with a curing temperature of 80-100°C and a curing time of 30-45 minutes.

5. The method for preparing a super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material according to claim 4, characterized in that: The step S1 of preparing the substrate layer specifically comprises the following steps: S1.1, Raw material preparation: weigh the isocyanate component and the hydroxyl-containing polyol component in the two-component polyurethane, mix them in a weight ratio of 1:1, weigh the epoxy resin in proportion, so that the total weight of the two-component polyurethane and the epoxy resin accounts for 40%-60% of the total weight of the waterproof membrane; S1.2, catalyst addition: add amine catalyst, accounting for 0.1%-1% of the total weight, and stir evenly; S1.3, heating and cross-linking reaction: heat the mixture to 60-80°C and maintain for 30-60 minutes; S1.4, Reaction process: Isocyanate groups react with hydroxyl groups of polyols to form urea bonds, epoxy groups open the ring, and cross-link with hydroxyl groups of polyurethane; S1.

5. Cooling: After the reaction is completed, the substrate layer is cooled to room temperature.

6. The method for preparing a super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material according to claim 4, characterized in that: The step S2 of preparing the self-adhesive layer specifically comprises the following steps: S2.

1. Raw material preparation: Weigh polyacrylate and amino-containing silicone in a weight ratio of 1:1, so that the total weight of the self-adhesive layer accounts for 20%-30% of the total weight of the waterproof membrane; S2.2, pH and temperature control: Use buffer solution to adjust the pH value of the solution to 4-6 and heat to 40-50℃; S2.3, sol-gel reaction: under the temperature and pH conditions, polyacrylate and siloxane undergo sol-gel reaction to form an organic-inorganic hybrid network structure, during which the hydroxyl groups in the siloxane molecules condense to form Si-O-Si bonds, and cross-link with the acrylate groups through covalent bonds and hydrogen bonds; S2.4, stirring and reaction time: the reaction time is controlled at 30-60min, and stirring is performed; S2.5, coating: evenly coating the formed self-adhesive layer on the cooled substrate layer.

7. The method for preparing a super weather-resistant self-adhesive polymer self-adhesive film waterproofing coiled material according to claim 4, characterized in that: The preparation of the mucosa in step S3 specifically comprises the following steps: S3.

1. Raw material preparation: weigh polyvinyl alcohol and boric acid in proportion so that the total weight of the sub-adhesive film accounts for 5%-10% of the total weight of the waterproof membrane, of which the proportion of polyvinyl alcohol is 3%-5% and the proportion of boric acid is 2%-5%; S3.2, mixing and dissolving: dissolving polyvinyl alcohol and boric acid in water and stirring evenly; S3.3, cross-linking reaction: stirring at room temperature for 10-20 minutes to allow the hydroxyl groups of the polyvinyl alcohol to undergo a cross-linking reaction with the boric acid to form a cross-linking structure of borate ester bonds; S3.4, coating: evenly coating the self-adhesive film formed by the reaction on the surface of the self-adhesive layer.

8. The method for preparing a super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material according to claim 4, characterized in that: The step S4 of adding the self-repairing microcapsules specifically comprises the following steps: S4.

1. Raw material preparation and dispersion: weigh the self-repairing microcapsules according to 1%-3% of the total weight of the waterproof membrane; S4.2, uniform dispersion: the self-healing microcapsules are uniformly dispersed in the substrate layer, using a low speed of 300-500 rpm stirring; S4.3, Microcapsule reaction process: Titanium dioxide generates free radicals under ultraviolet light, which trigger the rupture of the polyurea-polyurethane shell of the microcapsule and release the internal repair agent.

9. The method for preparing a super weather-resistant strong self-adhesive polymer self-adhesive film waterproofing coiled material according to claim 4, characterized in that: The step S5 specifically includes the following steps: S5.

1. Raw material preparation: weigh aliphatic polyamide and amine crosslinking agent according to 5%-10% of the total weight of the waterproof membrane, of which aliphatic polyamide accounts for 3%-7% and amine crosslinking agent accounts for 2%-3%; S5.2, mixing and dispersing: adding aliphatic polyamide and amine crosslinking agent into the substrate layer and stirring evenly; S5.3, curing and cross-linking reaction: heat the mixture to 80-100°C, maintain for 30-45 minutes, and perform cross-linking reaction; S5.

4. Cooling: After curing is completed, cool the waterproof membrane to room temperature.

10. The method for preparing a super weather-resistant self-adhesive polymer self-adhesive film waterproofing coiled material according to claim 5, characterized in that: The amine catalyst in step S1.2 is optionally selected from triethylamine and diethyltoluidine.